De ruïne van Brederode (Bulletin KNOB, 1990)
The castle of Brederode was built about 1300. The castle's regular plan makes one suspect a simple building history. Historical research however proved the building history of the castle to contain at least seven building phases. It is remarkable that most of these phases comprise renewal c.q. heightening of extant walls. Therefore after 1300 the plan of the castle has not changed radically. The castle decayed from 1500 on. The ruins has been excavated and restored since 1862. Missing mural works with loop-holes and other building traces have been reconstructed according to 19th century insights on a defensible castle. Thereby occasionally one did violence to the castle's architectural characteristics.As the only water-castle in Holland at present Brederode possesses an inner square with two levels, which has been caused by incorrect interpretations during the excavations. Because of this inner square and many other at the time executed building traces Brederode is a unique document. Thus the 20th century protectioner of monuments acquires insight into the problems the 19th century restoration pioneers were confronted with.The ruins of Brederode still contain many interesting building traces, which survived the decay from 1600 on both and the sometimes not very careful restorations of 1862. Part of these building traces tells on the story of the building history, another part on the way of building and the castle's function. Traces which indicate the way of building are the usage of chain-beams to strengthen the masonry and the walling up of couplings as basis for hanging scaffolds.In 1464 the comfort of the donjon has been improved by the making of wooden draught porches at the junctions with the stair-tower. The restoration is being looked at critically by pointing at the wrong reconstruction of the windows in the donjon and the continually changing shape of the south-west tower, which changes came into being because of the missing of data with respect to the tower's appearance. Some details cannot be explained such as the many toilet-tubes the castle possesses.